Kidney Functions and Physiological Complications in Pediatric Thalassemia Patients of Indian Origin - Andhale, Ramnath; Abrar Ahmad, Syed; Lodha, Sangita; Wankhade, Varsha (International Journal of Psychosocial Rehabilitation, 2019)
Background: Thalassemia patients develop progressive anemia and require regular blood transfusions to sustain life, as adverse effects start with hemolysis of red blood cells (RBCs). Objectives: The present study elucidates physiological complications and the effect of hypoxic stress on the physiology of kidney function in pediatric thalassemia. Methods: The current study includes 45 thalassemia patients of age between 3 and 16 years. A sufficient number of urine and blood samples were obtained from all the participants. Samples were analyzed for the biochemical parameters such as pH, creatinine, protein, urea, sodium (Na+), potassium (K+), uric acid, ferritin, albumin, hemoglobin, fetal hemoglobin, and malonaldehyde (MDA). Physiological complications were also investigated with the help of patient data sheet, blood and urine biochemical investigations and microscopic examinations of urine. Results: Most of the patients show severe physiological complications, including recurrent fever, joint and chest pain, shortness of breath, swelling of the abdomen, and an unusual headache. Serum creatinine level, serum uric acid, and hemoglobin levels in thalassemia are lower, while fetal hemoglobin levels are significantly elevated in thalassemia patients. Urine protein value, creatinine level, urea, and MDA were significantly high in thalassemia patients. High molecular weight proteins ranging from the molecular weight 10-260 kDa appeared in the urine of thalassemia patients. Conclusion: Most of the urine and serum biochemical parameters are significantly altered, indicating glomerular dysfunction may be due to glomerular damage, tubular damage, and nephritis.